Wybrane techniki manipulacji społecznej - Hamer, Hanna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2001)
The main purpose of the article, in which different methods of manipulations have been presented, is both decreasing the probability of unwanted social dependence and increasing the self-consciousness in that subject. Following verbal techniques: "even a penny will help", "why don't you want to help me?", untypical request, labeling effect and asking about feelings have been discussed. Manipulations based on the form, such as: speed of speaking, dilution effect, argumentation sequence and break of communication, have been characterized.